Effects of business jihad on entrepreneurs’ motivation and performance - Kedah, Zulkarnain; Anwar, Md. Aftab; Sarif, Suhaimi Mhd; Osman-Gani, AAhad M. (Inderscience Enterprises Ltd., 2019)
The concept of business Jihad has gained popularity among Muslim entrepreneurs in a different perspective. This concept has been highly misconceived in many aspects not only by non-Muslims, but among some Muslims as well. Despite a pivotal role business Jihad can play in the development of modern organizations, there is a dearth of valuable information regarding business Jihad and its effects on entrepreneurial outcomes. The objective of this qualitative study is to explore the effects of business Jihad on entrepreneurs’ motivation and performance by using in-depth interview methods. To achieve this, nine experienced and successful Muslim entrepreneurs in Malaysia were selected to participate in the research. This study found a clear perspective regarding the application of business Jihad among the Muslim entrepreneurs. Moreover, they consider entrepreneurship as a religious obligation to seek the pleasure of Allah rather than just a means to attain self-enrichment. It was further revealed that business Jihad positively influenced the attitudes of the participants who were inspired by its philosophy, thus that served as a catalyst not only for increasing motivation but also for improving performance. Implications of these findings are discussed for theoretical and practical implications in today’s dynamic business world. Recommendations for government policies and potential areas of future research are also outlined.